Zoom Cloud Meetings: Online Learning Media in Listening - Maskana, Nurul; Ilma, Ridha; Manalulaili, Manalulaili (ENGLISH FRANCA : Academic Journal of English Language and Education, 2022)
Zoom Cloud Meetings is a web-based learning platform that was utilized during the COVID-19 epidemic as a learning tool. The purpose of this study was to find out what students at UIN Raden Fatah Palembang felt about utilizing Zoom Cloud Meetings as a medium for learning and listening during the epidemic. A qualitative case study research technique was used in this study. The participants in this study were third-semester EFL students from UIN Raden Fatah Palembang's English education study program, with four students employing a deliberate sample using maximum variance sampling. The data was gathered using a semi-structured interview with open-ended questions. The theme analysis approach was used to analyze the data. The study's findings revealed the following benefits and drawbacks of using Zoom Cloud Meetings for listening skill development: (1) the influence of the first language on listening skills, (2) Zoom Cloud Meetings features, (3) internet connection, (4) security issues, (5) time limitation, (6) lack of vocabulary mastery, (7) homophone words, and (8) prior knowledge about the topics. As a result, the study's findings revealed the following benefits and drawbacks of using Zoom Cloud Meetings in learning to listen: the influence of the first language on listening skills, Zoom Cloud Meetings features, internet connection, security issues, time constraints, lack of vocabulary mastery, homophone words, and prior knowledge about the topics.Â